2015
DOI: 10.1007/s12598-015-0503-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ZrO2 ceramic coatings on ZrH1.8 prepared in different electrolytes by micro-arc oxidation

Abstract: ZrO 2 ceramic coatings were directly prepared on the surface of ZrH 1.8 in silicate and phosphate electrolytes by micro-arc oxidation (MAO) technique, respectively. The microstructure, chemical composition and phase composition of ZrO 2 ceramic coatings were investigated by X-ray diffraction (XRD), energy-dispersive spectrometry (EDS) and scanning electron microscopy (SEM). The anti-permeation effect was measured by means of vacuum dehydrogenation experiment. It is found that the coating fabricated in phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…The film formed by zirconium hydride in the atmosphere of CO 2 + P had a better hydrogen resistance effect. In the follow‐up study, some scholars 20,21 studied the hydrogen resistance mechanism of the film prepared by CO 2 in‐situ oxidation method: it was proposed that the tetragonal zirconia played the role of hydrogen resistance in the oxide layer, because it was continuous and compact, and because the OH bond formed between the O and H of the film, it could also prevent the escape of hydrogen.…”
Section: Main Problems Of Moderator Materialsmentioning
confidence: 99%
“…The film formed by zirconium hydride in the atmosphere of CO 2 + P had a better hydrogen resistance effect. In the follow‐up study, some scholars 20,21 studied the hydrogen resistance mechanism of the film prepared by CO 2 in‐situ oxidation method: it was proposed that the tetragonal zirconia played the role of hydrogen resistance in the oxide layer, because it was continuous and compact, and because the OH bond formed between the O and H of the film, it could also prevent the escape of hydrogen.…”
Section: Main Problems Of Moderator Materialsmentioning
confidence: 99%
“…Certainly, the selection of an oxide material with a coefficient of thermal expansion similar to that of the matrix is an important means of improving the hydrogen barrier properties of the coating. In recent years, zirconia (ZrO 2 ) has been widely studied as a new type of hydrogen permeation barrier coating material with a coefficient of thermal expansion much closer to those of various types of steel materials [ 24 , 25 ], and the diffusion coefficient of hydrogen in zirconia is low [ 26 , 27 , 28 ]. Hatano et al [ 29 ] prepared ZrO 2 coatings on ferrite steel by the sol-gel method and electrolytic deposition technique, and the coatings showed a good hydrogen barrier effect at 300–550 °C according to the gas phase hydrogen permeation test.…”
Section: Introductionmentioning
confidence: 99%
“…For example, He et al [21] prepared a Cr 2 O 3 coating on 316L stainless steel by the metal-organic decomposition (MOD) method, using chromium acetylacetonate as the precursor. The hydrogen permeation results show that the hydrogen permeability of Cr 2 O 3 coating can be reduced by 24-117 times at 823-973 K. Feng et al [22] deposited Al 2 O 3 as a hydrogen barrier coating on a 316L matrix by plasma electrolytic oxidation, and the results of gas-phase hydrogen permeation tests showed that the alumina coating was able to reduce the rate of hydrogen permeation by three orders of magnitude concerning the pure matrix. However, the thermal expansion coefficient between the metal matrix and the oxide coating differs greatly, and there is an obvious thermal mismatch problem, which is highly likely to lead to problems such as cracks and coating peeling.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-arc oxidation (MAO) is a technology that uses an in situ growth of ceramic coating directly on Al, Mg, Ti, and Zr surfaces. The oxide coating obtained by MAO is bonded to the metal closely, and the coating has good wear resistance, corrosion resistance, and electrical insulation properties [9][10][11].…”
Section: Introductionmentioning
confidence: 99%